2013
DOI: 10.1186/1475-2840-12-116
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating alpha-klotho levels are not disturbed in patients with type 2 diabetes with and without macrovascular disease in the absence of nephropathy

Abstract: BackgroundDiabetes is associated with a high incidence of macrovascular disease (MVD), including peripheral and coronary artery disease. Circulating soluble-Klotho (sKlotho) is produced in the kidney and is a putative anti-aging and vasculoprotective hormone. Reduced Klotho levels may therefore increase cardiovascular risk in diabetes. We investigated if sKlotho levels are decreased in type 2 diabetes and associate with MVD in the absence of diabetic nephropathy, and whether hyperglycemia affects renal Klotho … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 19 publications
2
23
4
Order By: Relevance
“…measured circulating α-klotho levels in diabetes patients. Although they reported that circulating α-klotho levels were not changed in diabetic patients compared to control, their sample size was very small ( n  = 35) and they never mentioned the albuminuria status of their diabetic patients [11]. In the present study, plasma α-klotho levels in patients with type 2 diabetes were highest in the normoalbuminuria stage and decreased with increasing urinary albumin excretion.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…measured circulating α-klotho levels in diabetes patients. Although they reported that circulating α-klotho levels were not changed in diabetic patients compared to control, their sample size was very small ( n  = 35) and they never mentioned the albuminuria status of their diabetic patients [11]. In the present study, plasma α-klotho levels in patients with type 2 diabetes were highest in the normoalbuminuria stage and decreased with increasing urinary albumin excretion.…”
Section: Discussioncontrasting
confidence: 63%
“…Recent studies in patients with diabetes report conflicting data. One study found serum α-klotho level was not significantly different between patients with diabetes without nephropathy and non-diabetic controls [11], [12]. In contrast, another study reports a significant reduction in serum klotho levels in patients with glycated hemoglobin (HbA1c) levels ≥6.5% compared to control samples (HbA1c <6.5%) [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reduced expression of Klotho in diabetes has been reported in experimental studies 11 12. In contrast, s-Klotho levels were not significantly different between patients with diabetes without nephropathy, and healthy controls 13. In these studies, patients have relatively preserved renal function.…”
Section: Discussionmentioning
confidence: 59%
“…After publication of this work [1], we noted that we inadvertently failed to include the complete list of all coauthors. The full list of authors has now been added and the Authors’ contributions and Competing interests section modified accordingly.…”
Section: Correctionmentioning
confidence: 99%